2008
DOI: 10.1007/s00423-008-0445-9
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotics, probiotics, synbiotics in surgery—are they only trendy, truly effective or even dangerous?

Abstract: The existing randomized controlled trials demonstrated a positive effect of synbiotics in patients with high-risk operations; however, synbiotic preparations should be extensively tested before using them in clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
28
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 67 publications
3
28
0
4
Order By: Relevance
“…Smiricky-Tjardes et al (2003) observed an increase in Bifidobacterium and Lactobacillus genera numbers in the intestine, a concomitant increase in SCFA concentration and improved small intestine morphology (Rayes et al, 2009). Fructoologosaccharides and galactooligosac- (Gibson et al, 1995;Zimmermann et al, 2001).…”
Section: Prebioticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Smiricky-Tjardes et al (2003) observed an increase in Bifidobacterium and Lactobacillus genera numbers in the intestine, a concomitant increase in SCFA concentration and improved small intestine morphology (Rayes et al, 2009). Fructoologosaccharides and galactooligosac- (Gibson et al, 1995;Zimmermann et al, 2001).…”
Section: Prebioticsmentioning
confidence: 99%
“…They have been referred to as the bifidus factor, because they support the growth and/ or activities of probiotic microorganisms in the gastrointestinal tract (Gibson and Roberfroid, 1995;Gibson, 2004;Marinho et al, 2007;Rayes et al, 2009).…”
Section: Prebioticsmentioning
confidence: 99%
“…[18][19][20] Most notably, some probiotics and prebiotics can stabilize the intestinal barrier and prevent bacterial translocation and infections. 21 In the intestinal lumen, probiotics ferment prebiotics, which leads to the production of butyric acid and other SCFAs. Moreover, IV administration of SCFAs ameliorated mucosal atrophy, 22 and butyric acid-supplemented PN (Bu-PN) both increased intestinal mucosal protein synthesis 23 and stimulated the growth of jejunal and ileal cells in a massive intestinal resection model.…”
Section: Original Communicationmentioning
confidence: 99%
“…Reduced gut microbial content may be associated with an impaired copyedited defense mechanism against pathogens and less environmental stimulation of the developing immune system of the digestive tract. Therefore, those submitted to extensive abdominal surgical procedures are at a particular risk [4,5]. Nosocomial bacterial infections still represent a major clinical problem in surgery despite advances in intensive care medicine, surgical skill and technology, and other related interventions.…”
Section: Introductionmentioning
confidence: 99%